2023
DOI: 10.1186/s12920-023-01446-6
|View full text |Cite
|
Sign up to set email alerts
|

Predicting gene knockout effects from expression data

Abstract: Background The study of gene essentiality, which measures the importance of a gene for cell division and survival, is used for the identification of cancer drug targets and understanding of tissue-specific manifestation of genetic conditions. In this work, we analyze essentiality and gene expression data from over 900 cancer lines from the DepMap project to create predictive models of gene essentiality. Methods We developed machine learning algorit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 21 publications
0
3
0
1
Order By: Relevance
“…To evaluate model performances, we used the Spearman rank correlation. While in the original DeepDEP paper Pearson correlation coefficients were computed, both methods are suited to evaluate this task (Rosenski, Shifman, et Kaplan 2023; Ma et al 2021). The Spearman correlation was preferred as it is more robust to outliers on non-normally distributed data (Hou et al 2022) and fits better the framework of ranking genes for target selection.…”
Section: Methodsmentioning
confidence: 99%
“…To evaluate model performances, we used the Spearman rank correlation. While in the original DeepDEP paper Pearson correlation coefficients were computed, both methods are suited to evaluate this task (Rosenski, Shifman, et Kaplan 2023; Ma et al 2021). The Spearman correlation was preferred as it is more robust to outliers on non-normally distributed data (Hou et al 2022) and fits better the framework of ranking genes for target selection.…”
Section: Methodsmentioning
confidence: 99%
“…Gene knockout prediction adds a critical perspective to our methodology, enabling researchers to predict how specific gene knockouts will influence the broader GRN. This task is instrumental in understanding the cascading effects of gene manipulation, as it reveals how knockouts in one gene can lead to changes in the expression of other genes[ 33 ]. By jointly optimizing these tasks, we gain a more comprehensive and holistic view of transcriptional regulation and gene knockouts within biological systems.…”
Section: Methodsmentioning
confidence: 99%
“…The DepMap database contains measurements of cellular proliferation after perturbation of all protein coding genes. It has been previously shown that for a given cell line, the gene expression profiles of the cell lines can be used to predict the gene essentiality scores [26,27]. Here, we carried out a similar approach, where gene expression profiles of genes across cell lines were used as input with a goal to reconstruct the cancer cell line dependency scores of the same genes.…”
Section: Cross-modality Learning: Transferring Knowledge Between Diff...mentioning
confidence: 99%